Principal Components by FTIR Spectroscopy as Innovative Characterization Technique during Differentiation of Pluripotent Stem Cells to Pancreatic Cells - Mata Miranda, M. M.; Guerrero Robles, C. I.; Rojas López, M.; Delgado Macuil, R. J.; González Díaz, C. A.; Sánchez Monroy, V.; Pérez Ishiwara, D. G.; Vázquez Zapien, G. J. (Revista Mexicana de Ingenieria Biomedica, 2017)
Two of the greatest challenges in Stem Cells (SCs) biology and regenerative medicine, are differentiation control of SCs and ensuring the purity of differentiated cells. In this sense, fast, efficient and accurate techniques for SCs characterization and their differentiation into different cell lineages are needed. The aim of this study was to analyse Pluripotent Stem Cells (PSCs) and Differentiated Pancreatic Cells (DPCs) by Fourier Transform Infrared (FTIR) spectroscopy and Principal Component Analysis (PCA). For this purpose, we differentiated PSCs toward DPCs, characterizing the differentiation process at different stages (0, 11, 17 and 21 days) through light microscopy and vibrational spectroscopy. FTIR spectra were analysed with the multivariate method of PCA, using the second derivatives in the protein, carbohydrate and ribose regions. The results indicate that the PCA allows to characterize and discriminate PSCs and DPCs at different stages of differentiation in the analysed spectral regions. From these results, we concluded that the PCA allows the chemically and structural characterization of PSCs and the different stages of their differentiation in a fast, accurate and non-invasive way.